Single-cell immunophenotyping revealed the association of CD4+ central and CD4+ effector memory T cells linking exacerbating chronic obstructive pulmonary disease and NSCLC - Gémes, Nikolett; Balog, József Á.; Neuperger, Patrícia; Schlegl, Erzsébet; Barta, Imre; Fillinger, János; Antus, Balázs; Zvara, Ágnes; Hegedűs, Zoltán; Czimmerer, Zsolt; Manczinger, Máté; Balogh, Gergő Mihály; et al. (Frontiers in Immunology, 2023)
Introduction: Tobacco smoking generated airway inflammation in chronic obstructive pulmonary disease (COPD) or its involvement in the development of lung cancer still among the leading causes of early death. Therefore, we aimed the better understanding of the disbalance in immunoregulation in chronic inflammatory conditions in smoker subjects with stable COPD (stCOPD), exacerbating COPD (exCOPD) or non-small cell lung cancer (NSCLC). Methods: Smoker controls without chronic illness were recruited as controls. Extensive mapping of single cells, surface receptor quantification was achieved by single-cell mass cytometry (CyTOF) with 29 antibodies. The CyTOF characterized 14 main immune subsets such as CD4+, CD8+, CD4+/CD8+, CD4-/CD8-, γ/δ T-cells, and other subsets such as: CD4+ or CD8+ NKT cells, NK cells, B-cells, plasmablasts, monocytes, CD11c dim , mDCs, pDCs. The CD4+ central memory (CM) T-cells (CD4+/CD45RA-/CD45RO+/CD197+), and CD4+ effector memory (EM) T-cells (CD4+/CD45RA-/CD45RO+/CD197-) were FACS sorted for RNAseq analysis. Plasma samples were assayed by Luminex MAGPIX ® for the quantitative measurement of 17 soluble immune-oncology mediators (BTLA, CD28, CD80, CD27, CD40, CD86, CTLA-4, GITR, GITRL, HVEM, ICOS, LAG-3, PD-1, PD-L1, PD-L2, TIM-3, TLR-2) in the studied four groups. Results: Our focus was on T-cell dependent differences in COPD and NSCLC, where peripheral CD4+ central memory and CD4+ effector memory cells showed significant reduction in exCOPD and the CD4+ CM showed elevation in NSCLC. The transcriptome analysis delineated a perfect correlation of differentially expressed genes between exacerbating COPD and NSCLC derived peripheral CD4+ CM or CD4+EM cells. The measurement of 17 immuno-oncology soluble mediators revealed a disease associated phenotype in the peripheral blood of stCOPD, exCOPD, and NSCLC patients. Discussion: The applied single cell mass cytometry, whole transcriptome profiling of peripheral CD4+ memory cells and quantification of 17 plasma mediators provided complex data that may contribute to the understanding of the disbalance in immune homeostasis generated or sustained by tobacco smoking in COPD and NSCLC.